Relationship between changes of swimming velocity, stroke rate, stroke length and muscle activities in front crawl swimming - Ikuta, Y.; Matsuda, Y.; Yamada, Y.; Kida, N.; Oda, S. (Japanese Journal of Physical Fitness and Sports Medicine, 2010)
The aim of this study was to investigate the relationship between changes in swimming velocity (SV), stroke rate (SR), stroke length (SL) and muscle activities during a 4×50m swimming test to simulate a 200m freestyle race. A total of 20 male collegiate swimmers participated in this study. The electromyography (EMG) signals of 11 muscles, 7 muscles in the upper half of the body and 4 muscles in the lower half, were recorded with surface electrodes. SV, SR and SL were analyzed for each 50m (S1, S2, S3 and S4) from side view recordings of swimmers taken with an underwater camera. SV and SR for S1 were significantly higher than for S2 and S3. SL for S1 was significantly longer than for S3. The averaged EMGs (aEMGs) for S1 were significantly higher than for S2 or for S3 in 5 muscles (flexor carpi ulnaris, biceps brachii, triceps brachii, deltoideus posterior and rectus femoris). There were no significant changes between S3 and S4 in SV, SR, SL and aEMG of all muscles except pectoralis major which showed the highest aEMG in S4. Significant correlations were observed between changes of (?) aEMG and ?SV, especially in upper half muscles (r=0.485-0.939, p<0.05). These results suggested that decline in muscle activities of the five muscles mentioned earlier caused a decrease in SV from S1 to S3; and an increase in muscle activity of the pectoralis major led preventing a decline in SV by maintaining the SR in S4.